THE EFFECT OF MOTIVATION, CAREER DEVELOPMENT, AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT PT. BANK SULUTGO IN TAGULANDANG - Taghulihi, Iin Angelia (Sam Ratulangi University, 2015)
ABSTRACT Employee performance is a very important aspect to be noticed by the company, because of the employees performance will affect the quality and quantity in the face of competition. To produce a quality performance of employees at the PT. Bank Sulutgo Tagulandang then that should be accompanied by motivation, career, and work discipline of employees in the PT. Bank Sulutgo Tagulandang. In achieving this it is indispensable a good relationship between the leadership of the PT. Bank Sulutgo Tagulandang with employees so that every employee has the urge to do a job that has been given. PT. Bank Sulutgo Tagulandang are expected to develop and encourage the motivation of the employees who work in order to do a job that produces a good employee performance achievement. The purpose of this research is to analyze and determine the effect of motivation, career development, and work discipline on employee performance â(Case Study at PT. Bank Sulutgo in Tagulandang). The result of this research Based on the results of research in the field Bank Sulutgo Tagulandang employee performance is influenced by motivation, career, and work discipline. Keywords: Motivation, Carrer Development, Work Discipline, Employee Performance